Development of Integrated Thematic Learning Based on Seesaw in Fifth-Grade Elementary School - Mhd Ridha; Fetri Yeni J; Darnis Arief; Desyandri Desyandri (AL-ISHLAH: Jurnal Pendidikan, 2023)
The use of smartphones in students' daily lives causes low student motivation to learn, especially after the Covid-19 pandemic. Students prefer to use their smart phones rather than studying. This causes low student learning outcomes. Innovative learning activities that make smartphones a fun learning medium for students are needed. The Seesaw digital class can be a solution to this problem. Therefore, this study explains the validity, practicality, and effectiveness of the Seesaw digital class in fifth-grade elementary schools. This research is a development research with a 4-D model. The participants were fifth-grade students from Cluster One Baso District, Agam Regency. The data collected in this study are validity data, practicality data, and data on the effectiveness of the Seesaw digital class. The data collection instruments used were questionnaires and interview sheets. The data obtained was then analyzed in the form of quantitative calculations and descriptive analysis. This development research produced a product in the form of Seesaw-based integrated thematic learning in elementary schools. The results of product validation in the form of Seesaw-based integrated thematic learning tools show that the product is valid based on the assessment made by the validator in a very valid category. The results of teacher responses and student responses for practicality with very practical categories. The results of the effectiveness test were seen from the learning outcomes of students who also increased. This shows that Seesaw-based integrated thematic learning is suitable for use in fifth-grade elementary schools.